KAJIAN SIFAT FISIK DAN KIMIA TANAH PADA TANAH BERPASIR DI DESA NOONGAN KECAMATAN LANGOWAN BARAT - Randy W.G. Tewu; Lientje Th. Karamoy; Diane D. Pioh (Universitas Sam Ratulangi, 2016)
ABSTRACTThe nature of soil is crucial in supporting the growth and development of plants, both the physical, chemical and biological soil. The physical properties of the soil, among others, the texture, structure and soil permeability. Soil chemical properties include soil pH and nutrient content. Nutrient content, consisting of the content of nitrogen, phosphorus, potassium and organic matter. Among other biological properties of soil microorganisms decomposing organic matter in the soil. The need for analysis of the nature of the soil to support plant productivity and prosperity. This study aims to determine the physical and chemical properties of soil on sandy soil in the village of Noongan District Langowan West. The method used is survey method with direct observations in the field and determining the location of the soil sampling. Sampling was done by making minipit with a size of 50cm x 50cm x 50cm in the field, to determine the physical and chemical properties of soil on sandy soil in the Village of Noongan District Langowan West. The study lasted for two months from February to March 2016 and held in the village as the center Noongan seasonal crops in the District of West Langowan. Further analysis of the soil at the Laboratory of Physics and Soil Conservation and Soil Fertility Laboratory of Chemistry and the Faculty of Agriculture, University of Sam Ratulangi to determine the physical and chemical properties of land on sandy soil.Keywords : sandy soil, physical and chemical properties of soil